Diskursus Pluralisme dalam Perspektif Hermeneutika Lintas-Iman: Penafsiran Q.S. Āli-‘Imrān (3): 19 dan Yohanes 14: 6 - Muhammad Radya Yudantiasa (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
This article problematizes the idea of pluralism in the Qur'an and Bible. The contestation about idea of pluralism often occurs in religion, especially in Islam and Christianity. This discourse will be analyzed using inter-religious hermeneutics perspective. This perspective shows that the relationship between the two holy books is a mutual connection. There are two options from my exploration about the idea of pluralism in the Qur'an and Bible. Firstly, make an inclusive interpretation of verses that are literally exclusive (Q.S. Āli-‘Imrān (3): 19 and John (14): 6) using the hermeneutic method. Secondly, understanding the two verses literally, but we must open ourselves to dialogue with others. The second option uses the inter-religious hospitality method. Both options are very relevant if implemented in the context of diversity in Indonesia.